Pengaruh Minat dan Program Pelatihan terhadap Pemanfaatan Sistem Informasi Manajemen serta Implikasinya terhadap Kinerja Karyawan di Rumah Sakit Intan Medika Lamongan - Pratiwi, Ema Vika; Paramarta, Vip; Rulia, Rulia; Yuliaty, Farida; Syahidin, Rukhiyat (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study evaluates the impact of interest and training on the use of management information systems and its implications for employee performance at Intan Medika Lamongan Hospital. Based on performance data showing that the Bed Occupancy Rate (BOR) is still suboptimal, this research identifies the lack of training as one of the main factors. The method used is a quantitative approach with path analysis, correlation coefficients, and coefficient of determination. The results of the study reveal that both interest and training have a significant effect on the utilization of the management information system and employee performance. Training has a greater impact on employee performance (37.8%) compared to interest (3.1%). Therefore, it is recommended to evaluate human resource management to improve the quality and integrity of employees.